التراث والحداثة في فكر محمد الجابري (Journal of Academic Research, 2023)
The concept of Arab heritage has received a considerable attention from thinkers and intellectuals, where many attitudes revealed themselves towards this concept. Some of them were proponent, some were opponent; to Heritage. Some of them advocated that the heritage is the source/root of every civilization, advancement, and progress, others calls to disavow the heritage. Among these trends, stands out the attitude of the Moroccan thinker, Mohamed Aljabri, who had a new vision represented in making the ends of the novel and the ancient meet. This research seeks to display the most significant  ideas introduced by him, and explain his reconciliatory theory which sustain new approach of thinking,  how he  attempted to reconcile between the ancient and novel, how he directed his thoughts to define the meaning of "heritage", how he presented "heritage" in a contemporary way, that is modernism for ALJABRI is not something monopolized be someone, rather it is a human phenomenon pursuing to modernizing people without negatively affecting their established assets and social values.